Unveiling the Power of Adaptive InformationTechnology: A Catalyst for Elevating SME Performance in Indonesia – A Case Study in Malang City - Ghozali Maski; Rachmad Kresna Sakti; Yenny Kormitasari; Amalia Rahmawati; Ghifary Duyufur Rohman (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
This research seeks to comprehend the impact of information technology (IT) utilization on the performance of Small and Medium Enterprises (SMEs) in Malang. The study investigates the perceptions of SMEs stakeholders through a survey involving 90 SMEs respondents in Malang. Employing a questionnaire and utilizing the Partial Least Squares Structural Equation Modeling (PLS-SEM) method for data analysis, the research reveals positive and significant outcomes for latent variables such as performance expectations, business expectations, social influence, hedonic motivation, and habits concerning SMEs behavior in adopting information technology, based on the Unified Theory of Acceptance and Use of Technology (UTAUT 2). However, the latent variable of price value does not exert a significant influence on SMEs behavioral interest in adopting information technology. Additionally, SMEs behavioral interest positively and significantly influences their usage behavior in utilizing information technology, and the subsequent usage behavior has a positive and significant effect on SME performance.